Distribution Patterns of Exotic Plant Chromolaena odorata, in Rehabilitation Zone at Donglo Block, Resort of Wonoasri, Meru Betiri National Park - Dwi Wardatul Rizkiah; Hari Sulistiyowati; Arif Mohammad Siddiq (Jurnal Riset Biologi dan Aplikasinya, 2021)
Exotic plants are plants that are introduced intentionally or unintentionally from their original habitat to a new habitat. One of the exotic plants that is potentially invasive is Chromolaena odorata. These plants are found a lot especially in the rehabilitation zone at Donglo Block Resort of Wonoasri, Meru Betiri National Park (MBNP). An initial effort to determine whether this exotic plant was potentially invasive was to use the distribution pattern of a plant population. This study aimed to determine the distribution pattern and area of cover of exotic plants C. odorata in rehabilitation zone at Donglo Block, Resort of Wonoasri MBNP. The sampling of C. odorata used the transect plot method systematically, which carried out in Donglo Block Resort of Wonoasri MBNP. Data analyzed using Morisita index. The map of distribution pattern of C. odorata was created using the Geographic Information System (GIS). Based on the results of the Morisita index, the value (IÎ´) = 12.39, which means that C. odorata has a clumped distribution pattern. The distribution pattern of C. odorata can also be seen from the visualization of the spatial distribution map, which shows that the growth of C. odorata in plants or overlaps with each other, hence that it looks clustered. The coverage area of C. odorata in the study location was 596,5 m2 or 29.24% of the total area of the study (20,400 m2). Based on the results of the coverage area of C. odorata, it was indicated that this exotic species is not yet classified as an invasive species in the area.